Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1083/jcb.135.1.19
|View full text |Cite
|
Sign up to set email alerts
|

The organization of endoplasmic reticulum export complexes.

Abstract: Abstract. Export of cargo from the ER occurs through the formation of 60-70-nm COPII-coated vesicular carriers. We have applied serial-thin sectioning and stereology to quantitatively characterize the three-dimensional organization of ER export sites in vivo and in vitro. We find that ER buds in vivo are nonrandomly distributed, being concentrated in regional foci we refer to as export complexes. The basic organization of an export complex can be divided into an active COPIIcontaining budding zone on a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
412
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(439 citation statements)
references
References 56 publications
21
412
0
1
Order By: Relevance
“…The addition of Sar1-GTP and RLC led to a dramatic recruitment of Sec13, as observed by the characteristic punctate staining, which represents newly assembled COPII carriers. These structures were identified previously as vesicular tubular clusters (VTCs) that form during COPII budding (Saraste and Svensson, 1991;Bannykh et al, 1996). Because the activated Sar1-GTP inhibits COPII uncoating, these COPII-coated vesicles fail to form mature VTCs and appear attached to each other as elongated "beads on a string," structures that are located at ER export sites (Bannykh et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of Sar1-GTP and RLC led to a dramatic recruitment of Sec13, as observed by the characteristic punctate staining, which represents newly assembled COPII carriers. These structures were identified previously as vesicular tubular clusters (VTCs) that form during COPII budding (Saraste and Svensson, 1991;Bannykh et al, 1996). Because the activated Sar1-GTP inhibits COPII uncoating, these COPII-coated vesicles fail to form mature VTCs and appear attached to each other as elongated "beads on a string," structures that are located at ER export sites (Bannykh et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…These structures were identified previously as vesicular tubular clusters (VTCs) that form during COPII budding (Saraste and Svensson, 1991;Bannykh et al, 1996). Because the activated Sar1-GTP inhibits COPII uncoating, these COPII-coated vesicles fail to form mature VTCs and appear attached to each other as elongated "beads on a string," structures that are located at ER export sites (Bannykh et al, 1996). Sar1 under these conditions is localized to these elongated sites, which contain recruited punctated Sec13 (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…In mammals, the distances are much longer. Most of the ER exit sites are in the cell periphery (Bannykh et al, 1996) and cargo must be transported 10 ,tm or more to the Golgi ribbon in the juxtanuclear region (Saraste and Svensson, 1991;Griffiths et al, 1995). Vesicles budding from the ER might need a representative of the Golgi apparatus nearby and such an outpost could be provided by the long form of syntaxin 5.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus possible that the membrane-bound ⑀-COP-depleted coatomer, although it lost at least part of its sorting capacity, conserved its ability to prevent premature fusion of transport intermediate. An extension of the transport model mentioned above predicts not only that TCs mature as they travel toward the Golgi complex but also that they could potentially fuse with each other to form the cis-Golgi network (5,62). Because we have shown that TC maturation is blocked by the inactivation of ⑀-COP (this work and Ref.…”
Section: Figmentioning
confidence: 99%